Dialogues in dance of Rosalia Merino-Santos in ballet, folk dance and modern dance. - Mercado, Mary Kathryn S.
This paper will point out the skills she has learned in ballet, folk dance and modern dance, their theoretical base and technical aspects. It will also tackle the premises of expression which are a big of her personal struggle as a student. This struggle was personal in so many ways as it was psychological and emotional as well. The barriers of hesitation broke themselves to an enlightenment that would change the way she looks at her whole life as person and as dancer. Her enlightenment in understanding brings brings to the fore the acceptance of the scientific basis of approach she learned in the University of Wisconsin under Margaret H'Doubler. This initiated her drive to contribute to the Philippine dance scene not anymore as a dancer but as an educator.